2020
DOI: 10.1111/cei.13441
|View full text |Cite
|
Sign up to set email alerts
|

Different subclasses and isotypes of antibodies against phosphorylcholine in haemodialysis patients: association with mortality

Abstract: Summary The risk of premature death is high among patients on haemodialysis (HD patients). We previously determined that immunoglobulin (Ig)M antibodies against phosphorylcholine (anti‐PC) are negatively associated with increased risk of cardiovascular disease (CVD), atherosclerosis, some autoimmune diseases and mortality among HD patients in this cohort. Here, we also study other subclasses and isotypes of anti‐PC in HD patients in relation to mortality, inflammation and gender. The study group is a cohort of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 50 publications
(73 reference statements)
2
12
0
Order By: Relevance
“…IgG1 and IgA anti-PC has similar properties as IgM anti-PC, associated with protection in atherosclerosis progress 29 . We have also reported that IgM and IgG1 anti-PC is associated with longevity in CKD 30 . Given the protection against arteriosclerosis in a dyslipidemic and uremic milieu we analyzed anti-PC and anti-MDA in paired summer (active state) and winter (hibernation) bear samples and report that anti-PC, especially IgA and IgG1 are strikingly high in hibernating bears in contrast to anti-MDA.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…IgG1 and IgA anti-PC has similar properties as IgM anti-PC, associated with protection in atherosclerosis progress 29 . We have also reported that IgM and IgG1 anti-PC is associated with longevity in CKD 30 . Given the protection against arteriosclerosis in a dyslipidemic and uremic milieu we analyzed anti-PC and anti-MDA in paired summer (active state) and winter (hibernation) bear samples and report that anti-PC, especially IgA and IgG1 are strikingly high in hibernating bears in contrast to anti-MDA.…”
mentioning
confidence: 56%
“…IgM anti-PC promote polarization of T regulatory cells, from atherosclerotic plaques, another immunomodulatory and anti-inflammatory property of anti-PC with direct relevance for the present study 33 . Moreover, IgG1, more than IgG2, anti-PC has protective properties associated with less atherosclerosis progress, less vulnerable plaques and mortality in CKD 29 , 30 , 34 and IgA anti-PC is associated with favorable atherosclerosis progress 29 . It is likely that IgA anti-PC also shares at least some of these protective properties with other anti-PC subclasses and isotypes but more studies on IgA anti-PC are warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, these findings have been confirmed by other researchers 20 25 , and extended to other chronic diseases as osteoarthritis 24 . Less is known about other subclasses and isotypes of anti-PC than IgM, even though we determined that IgG1, but not IgG2, shows comparable associations with protection as IgM, in atherosclerosis 13 , SLE 26 , and for mortality in CKD 11 .…”
Section: Discussionmentioning
confidence: 79%
“…Antibodies such as IgM, IgG1 and IgG2 to PC were determined by ELISA essentially as described previously 6 , 11 13 . Briefly, pooled serum from Sigma Aldrich (St Louis, MO, USA) was used as standard in each plate.…”
Section: Methodsmentioning
confidence: 99%